Evaluation and Design Public Facilities for People with Disabilities in Al-Hakim Mosque, Indonesia - Tri Putri, Nilda; Abrar, Rivandy; Fatrias, Dicky (Andalasian International Journal of Applied Science, Engineering and Technology, 2022)
Public facilities can be accessed by everyone, whether they have physical limitations or not.The Al-Hakim Mosque in Padang City is one of the facilities that is a place of worship for Muslims as well as a tourist attraction in West Sumatra.The research was conducted by identifying the inhibiting factors for persons with disabilities when using these facilities, designing these facilities to be easy to use by persons with disabilities (especially wheelchair users), and making a budget plan for making these facilities. Identification of inhibiting factors is done by making checklist to see the various obstacles experienced by wheelchair users and selecting anthropometric variables needed in designing public facilities. The results of this study are in the form of public facility designs that can be used by wheelchair users, the percentage of the suitability of these public facilities after the design is carried out, and the costs required to build these facilities